Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2010
DOI: 10.1145/1753326.1753543
|View full text |Cite
|
Sign up to set email alerts
|

Presenting diverse political opinions

Abstract: Is a polarized society inevitable, where people choose to be exposed to only political news and commentary that reinforces their existing viewpoints? We examine the relationship between the numbers of supporting and challenging items in a collection of political opinion items and readers' satisfaction, and then evaluate whether simple presentation techniques such as highlighting agreeable items or showing them first can increase satisfaction when fewer agreeable items are present. We find individual difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
163
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(172 citation statements)
references
References 20 publications
(21 reference statements)
4
163
0
5
Order By: Relevance
“…Tweets (or information provided on other social media sites) can be highlighted, filtered out, or sorted based on the similarity of their audiences' political preferences to those of the user. Alternatively, our method could be used as input to systems that recommend content read by audiences with diverse political opinions [10]. Finally, marketers and social media analysts can use our method to get a sense of their Twitter reach within different political markets, helping them know if they are reaching their intended audience.…”
Section: Discussionmentioning
confidence: 99%
“…Tweets (or information provided on other social media sites) can be highlighted, filtered out, or sorted based on the similarity of their audiences' political preferences to those of the user. Alternatively, our method could be used as input to systems that recommend content read by audiences with diverse political opinions [10]. Finally, marketers and social media analysts can use our method to get a sense of their Twitter reach within different political markets, helping them know if they are reaching their intended audience.…”
Section: Discussionmentioning
confidence: 99%
“…Communitarianism [15,46] emphasizes group identification with like-minded people in order to better organize against groups with whom they disagree. Evidence from studies of ideological fragmentation and selective exposure have demonstrated that communitarian behavior is exceedingly common both online and off, with most people choosing to engage material that aligns with their prior beliefs [18,27,28,35]. And while some people do not go out of their way to avoid challenging material, they still must encounter it first, an activity that platforms like Facebook and Google Reader do not encourage.…”
Section: Theory and Design For Public Deliberationmentioning
confidence: 99%
“…It is challenging for people to listen to perspectives that contradict their own; most people, at least in America, are averse to even engaging with those with whom they suspect of harboring different views [36]. The use of communication media reflect these tendencies, with people highly attracted to content that aligns with their prior beliefs, even those who do not actively avoid challenging content [18,27,28,35]. The problem is reinforced by a lack of effective socialization in the skills and values associated with productive exchanges of ideas, particularly in public schools [38].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that a majority of users are challengeaverse [46], so it could be expected that politically-engaged users exposed to our conditions would have had a negative (e. g., less engaging) experience. This was not the caseusers who were exposed to our proposed conditions and are politically-involved present a comparable (and even slightly more positive) experience when using the site.…”
Section: Overview Of Resultsmentioning
confidence: 99%
“…This direct approach has not been effective as users often do not value diversity or do not feel satisfied with it [46]. Motivated by this scenario, our work aims at understanding how to encourage exposure to diverse people from an ideological point of view on microblogging platforms.…”
Section: Introductionmentioning
confidence: 99%